2020
DOI: 10.7307/ptt.v32i4.3311
|View full text |Cite
|
Sign up to set email alerts
|

The Profitability Analysis of the Logistics Industry Companies in the Balkan Countries

Abstract: The main purpose of this paper is to research the factors that have an impact on the company profitability in the logistics industry during a five-year period (2013-2017). The sample includes 748 active companies operating in the logistics industry in the Balkan countries. Bearing in mind that logistics is an essential instrument of competitiveness and profitability of the company operations and that logistics is one of the most profitable industries, this paper used the panel data model with fixed effect in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…As a result, it might be assumed that LEV is one of the main elements influencing the increase in business profitability. This result has verified the findings generated by Boadi et al (2013) and Vuković et al (2020). The findings of these research have suggested that a rise in debt could result in an increase in the performance of the Malaysian courier firms' return on assets.…”
Section: Random Effects Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As a result, it might be assumed that LEV is one of the main elements influencing the increase in business profitability. This result has verified the findings generated by Boadi et al (2013) and Vuković et al (2020). The findings of these research have suggested that a rise in debt could result in an increase in the performance of the Malaysian courier firms' return on assets.…”
Section: Random Effects Resultssupporting
confidence: 89%
“…Leverage can best be described as a company using total assets to fund its projects or investments or as a source of financing (Vuković et al, 2020). In their research article, it has been found that a negative effect of leverage or low leverage on a company's profitability has been supported by many previous studies done.…”
Section: Leveragementioning
confidence: 98%
See 2 more Smart Citations
“…Profitability is the company's ability to generate profits, high profits indicate good company performance, thus encouraging the company to be able to complete financial performance reports on time [18]. Therefore, companies that can adapt quickly to changing circumstances are those that have a beneficial effect on profitability [19].…”
Section: Company Size Profitability Leverage and Operating Efficiencymentioning
confidence: 99%